2020
DOI: 10.1108/jec-01-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and MNCs: evidence from Morocco community

Abstract: Purpose This study aims to explore the relationship between transformational leadership and organizational commitment in multinational companies (MNCs) in Morocco. Design/methodology/approach The study used a sample size of 256 employees to attain results regarding a relationship between transformational leadership and organizational commitment. Proposed hypotheses are tested through regression analysis. Findings Findings show a relationship between transformational leadership and organizational commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 108 publications
1
8
0
Order By: Relevance
“…After verifying the SEM model, this study also conducted a regression verification of transformational leadership, CSR and OC, and found that the results were significant as the authors' proposal. This is consistent with previous findings in McMurray et al, 2010 ; Patiar and Wang, 2016 ; Tabassi et al, 2016 ; Allen et al, 2017 ; Khan et al, 2018 ; Palalic and Ait Sidi Mhamed, 2020 ). Since RDHL's practice of CSR provides a basis for organizational sustainability (Allen et al, 2017 ); it also positively impacts employee commitment and organizational evaluation (McMurray et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…After verifying the SEM model, this study also conducted a regression verification of transformational leadership, CSR and OC, and found that the results were significant as the authors' proposal. This is consistent with previous findings in McMurray et al, 2010 ; Patiar and Wang, 2016 ; Tabassi et al, 2016 ; Allen et al, 2017 ; Khan et al, 2018 ; Palalic and Ait Sidi Mhamed, 2020 ). Since RDHL's practice of CSR provides a basis for organizational sustainability (Allen et al, 2017 ); it also positively impacts employee commitment and organizational evaluation (McMurray et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…TL has positively influenced employee sustainability performance (Jiang et al, 2017 ). TL also has found a direct impact on the achievement of OC (Tabassi et al, 2016 ; Palalic and Ait Sidi Mhamed, 2020 ). Through OC, leadership style directly or indirectly affects social and environmental performance (Patiar and Wang, 2016 ) and can be used to respond to future challenges and promote the sustainable development of organizations (Jones et al, 2017b ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first one is having a manager that will run the business locally by which an international company is assimilated into the local culture without negative consequences. The other one is to adapt to the local culture as the international manager adapts to all cultural attributes [9,10] to have a successful business. Operating in the international market is truly complexed and challenging.…”
Section: Sustainability's Challenge 1: Cultural Environment and International Businessmentioning
confidence: 99%
“…Although these goals are related and can be met by transactions between the parties, there is no higher purpose that would connect the leader and followers (Burns, 1978). Transactional leaders set goals and use rewards and punishments to motivate the followers to perform (Firfiray et al , 2018; Palalic and Ait Sidi Mhamed, 2020). Transactional leadership is characterized by three different dimensions: contingent reward, management by exception, and laissez-faire leadership.…”
Section: Theoretical Framework and Propositionsmentioning
confidence: 99%